Differential Role of PTEN Phosphatase in Chemotactic Growth Cone Guidance - Henle, Steven J. (American Society for Biochemistry and Molecular Biology, 2013)
Negatively targeting the tumor suppressor and phosphoinositide phosphatase PTEN (phosphatase and tensin homologue) promotes axon regrowth after injury. How PTEN functions in axon guidance has remained unknown. Here we report the differential role of PTEN in chemotactic guidance of axonal growth cones. Down-regulating PTEN expression in Xenopus laevis spinal neurons selectively abolished growth cone chemorepulsion but permitted chemoattraction. These findings persisted during cAMP-dependent switching of turning behaviors. Live cell imaging using a GFP biosensor revealed rapid PTEN-dependent depression of phosphatidylinositol 3,4,5-trisphosphate levels in the growth cone induced by the repellent myelin-associated glycoprotein. Moreover, down-regulating PTEN expression blocked negative remodeling of β1-integrin adhesions triggered by myelin-associated glycoprotein, yet permitted integrin clustering by a positive chemotropic treatment. Thus, PTEN negatively regulates growth cone phosphatidylinositol 3,4,5-trisphosphate levels and mediates chemorepulsion, whereas chemoattraction is PTEN-independent. Regenerative therapies targeting PTEN may therefore suppress growth cone repulsion to soluble cues while permitting attractive guidance, an essential feature for re-forming functional neural circuits.